Hot melt adhesive for electronic products and preparation method thereof
By using composite polyols and modified fillers in hot melt adhesives, a dense molecular chain network and microporous structure is formed, which solves the problem of insufficient performance of existing hot melt adhesives and significantly improves its thermal stability and waterproofness. , meets the performance needs of electronic products.
Patent Information
- Application Number
- CN202411282424.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Existing hot melt adhesives for electronic products have shortcomings in high temperature stability, bonding strength, waterproofing, aging resistance and anti-static properties, and cannot meet the growing demand for electronic products performance.
Compositions such as composite polyols, modified fillers and specific tackifying resins are used to form dense three-dimensional molecular chain connection networks and microscopic active pore structures to improve the density and dispersion strength of hot melt adhesives, and to modify the surface of the filler. The adapter and reactive groups interact to enhance their uniformity and positional fixation in the hot melt adhesive system.
It significantly improves the thermal stability, adhesion, waterproofness and aging corrosion resistance of hot melt adhesives, extends its application environment in electronic products, and meets the performance requirements of electronic products for polyurethane hot melt adhesives.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of hot melt adhesives, and in particular to a hot melt adhesive for electronic products and a preparation method thereof. Background Art
[0002] Hot melt adhesive used in electronic products is an adhesive that becomes flowable, plastic and bonds various materials after heating. Once it cools and solidifies, it forms a strong bond for bonding. This type of adhesive is often used in the assembly and repair of electronic products because it can cure quickly and be used at lower temperatures, which helps avoid damage to temperature-sensitive electronic components.
[0003] Generally speaking, the characteristics of hot melt adhesive products include fast curing efficiency, easy use, strong adhesion and certain insulation, etc. In recent years, with the continuous evolution of the performance of electronic products and the continuous improvement of consumers' performance requirements for electronic products, the performance requirements of hot melt adhesive products in electronic products have also been challenged.
[0004] Existing electronic products usually require hot melt adhesive products to have high temperature stability, bonding strength and mechanical properties after curing, but not enough attention is paid to the hot melt adhesive's waterproof performance, aging resistance, corrosion resistance and antistatic performance. As a result, existing hot melt adhesive products, especially polyurethane hot melt adhesive, cannot effectively balance the above-mentioned required properties, thereby limiting the application environment of polyurethane hot melt adhesive in electronic products and failing to meet the growing demand for existing electronic products.
[0005] Therefore, in order to solve the above problems, the present application provides a hot melt adhesive for electronic products and a preparation method thereof. The hot melt adhesive for electronic products prepared in the present application not only has excellent curing efficiency, adhesion and mechanical properties, but also retains good waterproofness, aging resistance, corrosion resistance and other properties. It can meet the performance requirements of existing electronic products for polyurethane hot melt adhesive, expand the application environment of polyurethane hot melt adhesive in electronic products, and has very excellent application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a hot melt adhesive for electronic products. The raw materials, calculated by mass, are: 60 to 90 parts of complex polyol, 10 to 20 parts of tackifying resin, 15 to 25 parts of modified filler, 6 to 10 parts of plasticizer, 1.5 to 3 parts of chain extender, 5 to 12 parts of dispersant, 0.5 to 1.5 parts of catalyst, 3 to 5 parts of wetting agent, and 20 to 30 parts of isocyanate.
[0007] As a preferred solution, the mass ratio of the complex polyol, isocyanate and tackifying resin is (75-85): (22-26): (12-18).
[0008] As a preferred solution, the mass ratio of the complex polyol, isocyanate and tackifying resin is (78-84): (24-25): (14-16).
[0009] As a preferred solution, the mass of the composite polyol, modified filler and dispersant is (75-85): (18-24): (6-10).
[0010] As a preferred solution, the mass of the composite polyol, modified filler and dispersant is (78~84):(18~22):(7~8).
[0011] As a preferred solution, the composite polyol is a composition of highly active polyether polyol, polyester polyol and modified polyol.
[0012] As a preferred solution, the mass ratio of the highly active polyether polyol, polyester polyol and modified polyol is (1.8-2.4):(4-5.5):(1.3-1.6).
[0013] As a preferred solution, the mass ratio of the highly active polyether polyol, polyester polyol and modified polyol is (2-2.2): (4.2-5.2): (1.4-1.5).
[0014] As a preferred solution, the functionality of the highly active polyether polyol is 3.
[0015] As a preferred solution, the highly active polyether polyol is propylene oxide-ethylene oxide copolyether triol.
[0016] As a preferred solution, the mass fraction of ethylene oxide chain segments in the highly active polyether polyol is 10-20%.
[0017] As a preferred solution, the number average molecular weight of the highly active polyether polyol is 4000-6000 Da.
[0018] As a preferred solution, the polyester polyol is polyadipic acid polyester diol.
[0019] As a preferred solution, the number average molecular weight of the polyester polyol is 3500~4500 Da.
[0020] As a preferred solution, the modified polyol is PIPA modified polyether polyol.
[0021] As a preferred solution, the number average molecular weight of the PIPA modified polyether polyol is 5500-7000 Da.
[0022] As a preferred solution, the viscosity of the PIPA modified polyether polyol is 1500-3000 mPa·s at 25°C.
[0023] As a preferred solution, the viscosity of the PIPA modified polyether polyol is 1800-2500 mPa·s at 25°C.
[0024] The addition of the above-mentioned specific polyol composition selected in the present application can effectively improve the thermal stability, adhesion, water resistance, aging and corrosion resistance and other properties of the polyurethane hot melt adhesive. The high-activity polyether polyol added in the present application can greatly enhance the density of the hot melt adhesive system. The large number of active sites contained in it can continuously produce continuous line bonding with other raw materials during the formation of the hot melt adhesive system, and the active groups contained in it can interact with the active groups on the surface of the modified filler added in the present application to form a good connection force, so that the added modified filler can be used as a high-quality carrier in the process of polyurethane formation, thereby achieving uniform dispersion in the hot melt adhesive system, and the dispersion strength greatly enhances its position fixity in the system as the hot melt adhesive solidifies, thereby reducing its precipitation, segregation and aggregation. On the other hand, adding The combination of modified polyols and polyester polyols with high-activity polyether polyols can form an extremely dense and complex three-dimensional molecular chain connection network in the colloid system, and the construction of this network can cooperate with the modified filler to form a microscopic active pore structure. The existence of this structure can provide a dissipation path for the conduction of mechanics and heat, thereby maintaining good stability and performance under the action of external force and heat. The dense network formed and the joint action of the modified filler can effectively increase the free resistance of water molecules and free groups in the hot melt adhesive system, thereby greatly increasing the difficulty of its penetration and greatly reducing the probability of combination and contact between them, thereby maintaining excellent waterproof, aging and corrosion resistance and other properties during long-term use.
[0025] As a preferred solution, the tackifying resin is at least one of terpene phenolic resin, dicyclopentadiene resin, and C5 / C9 copolymerized petroleum resin.
[0026] As a preferred solution, the tackifying resin is terpene phenolic resin.
[0027] As a preferred solution, the preparation method of the modified filler comprises the following steps: S1: adding carbon fiber to deionized water, adding ethanol and adjusting the pH to 9-10 with ammonia water, then adding tetraethyl orthosilicate and isopropanol and heating to 70-75°C for 2-2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding the pretreated carbon fiber to DMF solution, adding succinic anhydride, sodium dodecylbenzene sulfonate and titanate coupling agent, heating to 65-70°C for reaction 2~3h to obtain pretreated particles; S3: add the pretreated particles and zinc nitrate into the DMF solution and stir to mix evenly, then add dropwise the DMF solution containing 2,5-dihydroxyterephthalic acid and titanium dioxide, the dropping time is 1~1.5h, and the temperature is raised to 70~80℃ and stirred at 80~120rpm for 3~5h, then continue to heat to 140~150℃, stir at 50~70rpm for 24~30h, and naturally cool to room temperature after completion, centrifuge and filter the product, wash and dry to obtain.
[0028] As a preferred solution, the mass ratio of the carbon fiber, ethanol, tetraethyl orthosilicate and isopropyl alcohol is (5.5-6): (1-1.5): (1.2-1.8): (0.1-0.2).
[0029] As a preferred solution, the mass ratio of the pretreated carbon fiber, succinic anhydride, sodium dodecylbenzene sulfonate and titanate coupling agent is (4-4.5): (1.5-2): (0.2-0.4): (0.1-0.2).
[0030] As a preferred solution, the titanate coupling agent is monoalkoxy titanate.
[0031] As a preferred solution, the mass ratio of the pretreated particles, zinc nitrate, 2,5-dihydroxyterephthalic acid and titanium dioxide is (2-2.5): (0.8-1): (3-4): (0.2-0.4).
[0032] As a preferred solution, the average particle size of the titanium dioxide is 5-15 nm.
[0033] As a preferred solution, the carbon fiber is chopped carbon fiber; the average diameter of the chopped carbon fiber is 5-8 μm; and the average length of the chopped carbon fiber is 15-20 μm.
[0034] The modified filler added in the present application can effectively improve the mechanical, waterproof, aging and corrosion resistance and other properties of the hot melt adhesive. The modified filler added in the present application can form an overall structure with chopped carbon fibers as the base and composite structure particles connected on the surface. The structure can form a good continuous stacking phenomenon through the spreading effect of the chopped carbon fibers in the hot melt adhesive system, and the active groups on the surface of the modified composite particles can provide a good basis for the flow and spreading of the modified filler through the good intermolecular interaction with the polyurethane system, thereby forming a good barrier system for water molecules and free groups in the polyurethane hot melt adhesive system, greatly reducing their collision, agglomeration and reaction probabilities, and on the surface of the hot melt adhesive, the surface of the carbon fiber loaded with framework particles can greatly increase the peak and valley surface structure coverage of the hot melt adhesive surface, thereby greatly reducing the formation efficiency of the hydration layer on the surface of the hot melt adhesive, and cutting off the continuous convergence between the local hydration systems, thereby greatly enhancing the isolation force of the hot melt adhesive surface for water molecules, thereby obtaining excellent waterproof, aging and corrosion resistance; on the other hand, the intermolecular connection force formed by the added modified filler and the system molecules can effectively help improve the upper limit of the internal stress tolerance of the hot melt adhesive system, thereby obtaining excellent mechanical properties.
[0035] As a preferred solution, the plasticizer is a combination of dioctyl phthalate and triethyl citrate.
[0036] As a preferred solution, the mass ratio of dioctyl phthalate to triethyl citrate is (3-4):(1-2).
[0037] As a preferred solution, the mass ratio of dioctyl phthalate to triethyl citrate is (3.2-3.5):(1.2-1.5).
[0038] As a preferred solution, the chain extender is at least one of ethanolamine, ethylenediamine, diethanolamine, triethanolamine, and 1,2-propylenediamine.
[0039] As a preferred solution, the chain extender is 1,2-propylenediamine.
[0040] As a preferred solution, the dispersant is a composition of lauryl alcohol polyoxyethylene ether and coconut oil betaine.
[0041] As a preferred solution, the mass ratio of lauryl alcohol polyoxyethylene ether to coconut oil betaine is (3-4): (0.5-0.8).
[0042] As a preferred solution, the mass ratio of lauryl alcohol polyoxyethylene ether to coconut oil betaine is (3-3.5): (0.6-0.7).
[0043] As a preferred solution, the catalyst is dibutyltin dilaurate or dibutyltin dioctoate.
[0044] As a preferred solution, the catalyst is dibutyltin dioctoate.
[0045] As a preferred solution, the wetting agent is a combination of sodium stearate and sodium lauryl sulfate.
[0046] As a preferred solution, the mass ratio of sodium stearate to sodium lauryl sulfate is (4-4.5): (1.5-2).
[0047] As a preferred solution, the isocyanate is at least one of hexamethylene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate.
[0048] As a preferred solution, the isocyanate is diphenylmethane diisocyanate.
[0049] The second aspect of the present application provides a method for preparing the above-mentioned hot melt adhesive for electronic products, which specifically includes the following steps: S1: Add complex polyols, catalysts, plasticizers and chain extenders into a reaction container, heat up to 65~75°C, stir at 60~80rpm for 3~5h, and then dry and remove water to a water content of ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 120~160rpm and heat to 110~130°C, keep warm for reaction for 3~5h, take out the product after the reaction is completed, vacuum degassing for 0.5~1h and transfer to a storage container for drying under inert gas protection.
[0050] The beneficial effects of this application are:
[0051] 1. The hot melt adhesive for electronic products provided in the present application not only has excellent curing efficiency, adhesion and mechanical properties, but also has good waterproofness, aging resistance, corrosion resistance and other properties. It can meet the performance requirements of existing electronic products for polyurethane hot melt adhesives, expand the application environment of polyurethane hot melt adhesives in electronic products, and has very excellent application prospects.
[0052] 2. A hot melt adhesive for electronic products provided in the present application, which uses a specific polyol composition to effectively improve the thermal stability, adhesion, water resistance, aging and corrosion resistance and other properties of the polyurethane hot melt adhesive; the added high-activity polyether polyol can greatly enhance the density of the hot melt adhesive system, and the large number of active sites contained in it can continuously produce continuous line bonding with other raw materials during the formation of the hot melt adhesive system, and the active groups contained in it can interact with the active groups on the surface of the modified filler added in the present application to form a good connection force, so that the added modified filler can be used as a high-quality carrier in the process of polyurethane formation, thereby achieving uniform dispersion in the hot melt adhesive system, and the dispersion strength greatly enhances its position fixity in the system as the hot melt adhesive solidifies, thereby reducing its precipitation, segregation and aggregation.
[0053] 3. A hot melt adhesive for electronic products provided in the present application, in which the modified polyols and polyester polyols added in combination with the highly active polyether polyols can form an extremely dense and complex three-dimensional molecular chain connection network in the colloid system, and the construction of the network can cooperate with the modified filler to form a microscopic active pore structure, the existence of which can provide a dissipation pathway for the conduction of mechanics and heat, thereby maintaining good stability and performance under the action of external force and heat, and the dense network formed and the joint action of the modified filler can effectively increase the free resistance of water molecules and free groups in the hot melt adhesive system, thereby greatly increasing the difficulty of its penetration, and greatly reducing the probability of combination and contact between them, thereby maintaining excellent waterproof, aging and corrosion resistance and other properties during long-term use.
[0054] 4. A hot melt adhesive for electronic products provided in the present application, wherein the modified filler added therein can form an overall structure with chopped carbon fibers as the base and composite structure particles connected on the surface, and the structure can form a good continuous stacking phenomenon through the spreading effect of the chopped carbon fibers in the hot melt adhesive system, and the active groups on the surface of the modified composite particles can provide a good basis for the flow and spreading of the modified filler through the good intermolecular interaction with the polyurethane system, thereby forming a good barrier system for water molecules and free groups in the polyurethane hot melt adhesive system, greatly reducing the probability of collision, agglomeration and reaction, and on the surface of the hot melt adhesive, the surface of the carbon fibers loaded with framework particles can greatly increase the peak and valley surface structure coverage of the hot melt adhesive surface, thereby greatly reducing the formation efficiency of the hydration layer on the surface of the hot melt adhesive, and cutting off the continuous convergence between the local hydration systems, thereby greatly enhancing the isolation force of the hot melt adhesive surface for water molecules. DETAILED DESCRIPTION
[0055] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0056] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0057] Example 1
[0058] Example 1 The first aspect provides a hot melt adhesive for electronic products. The raw materials, in parts by mass, are: 82.5 parts of complex polyol, 14.8 parts of tackifying resin, 19.5 parts of modified filler, 8.5 parts of plasticizer, 1.8 parts of chain extender, 7.6 parts of dispersant, 0.8 parts of catalyst, 4.2 parts of wetting agent, and 24.2 parts of isocyanate.
[0059] The composite polyol is a composition of high-activity polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 2.1:4.5:1.4.
[0060] The highly active polyether polyol is a propylene oxide-ethylene oxide copolyether triol with a functionality of 3, an ethylene oxide chain mass fraction of 16.2%, and a number average molecular weight of 5200 Da. It was purchased from Changhua Chemical Technology Co., Ltd. and is a CHE-330N product.
[0061] The polyester polyol is polyadipic acid polyester diol with a number average molecular weight of 4000 Da, which is purchased from the HY series of corresponding molecular weight products sold by Shandong Suihua Biotechnology Co., Ltd.
[0062] The modified polyol is a PIPA modified polyether polyol with a number average molecular weight of 6000 Da and a viscosity of 2200 mPa·s at 25° C. The SP50-04 product was purchased from Shell.
[0063] The tackifying resin is terpene phenolic resin, which is purchased from 803L terpene phenolic tackifying resin product sold by Shandong Changyao New Materials Co., Ltd.
[0064] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 5.8 parts of carbon fiber to 120 parts of deionized water, adding 1.4 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 1.6 parts of tetraethyl orthosilicate and 0.2 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 4.2 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 1.6 parts of succinic anhydride, 0.26 parts of sodium dodecylbenzene sulfonate and 0.18 parts of titanate couple The mixture was heated to 68°C and kept warm for 2.5 hours to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 1 part of zinc nitrate were added to 80 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 3.2 parts of 2,5-dihydroxyterephthalic acid and 0.35 parts of titanium dioxide (40 parts in total) was added dropwise for 1 hour, and the mixture was heated to 75°C and stirred at 100 rpm for 4 hours, and then the mixture was heated to 140°C and stirred at 60 rpm for 28 hours. After completion, the mixture was naturally cooled to room temperature, and the product was centrifuged, filtered, washed and dried to obtain the product.
[0065] The titanate coupling agent is monoalkoxy titanate KR-TTS.
[0066] The average particle size of titanium dioxide is 10.5 nm.
[0067] The carbon fiber is chopped carbon fiber with an average diameter of 6.5 μm and an average length of 18.2 μm, and is purchased from Shanghai Lishuo Composite Materials Co., Ltd.
[0068] The plasticizer is a composition of dioctyl phthalate and triethyl citrate, and the mass ratio of the two is 3.3:1.2.
[0069] The chain extender is 1,2-propylenediamine; the catalyst is dibutyltin dioctoate.
[0070] The dispersant is a composition of lauryl alcohol polyoxyethylene ether and cocoyl betaine, with a mass ratio of 3.4:0.6; lauryl alcohol polyoxyethylene was purchased from the MOA-5 model product sold by Hai'an Guoyun Chemical Co., Ltd.; cocoyl betaine was purchased from the cocamidopropyl betaine CAB-35 product sold by Jiangsu Haolong Chemical Co., Ltd.
[0071] The wetting agent is a composition of sodium stearate and sodium lauryl sulfate, and the mass ratio of the two is 4.2:1.6.
[0072] The isocyanate is diphenylmethane diisocyanate.
[0073] The second aspect of this embodiment provides a method for preparing the above-mentioned hot melt adhesive for electronic products, which specifically includes the following steps: S1: Add complex polyols, catalysts, plasticizers and chain extenders into a reaction container, heat to 70°C, stir at 80rpm for 4h, and then dry and remove water to a water content of ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 140rpm and heat to 120°C, keep warm for 4.5h, take out the product after the reaction is completed, vacuum degas for 1h and transfer to a storage container for drying under inert gas protection.
[0074] Example 2
[0075] Example 2 The first aspect provides a hot melt adhesive for electronic products. The raw materials, calculated by mass, are: 78.5 parts of complex polyol, 12.2 parts of tackifying resin, 23 parts of modified filler, 7.5 parts of plasticizer, 1.6 parts of chain extender, 9.8 parts of dispersant, 0.8 parts of catalyst, 3.8 parts of wetting agent, and 22.6 parts of isocyanate.
[0076] The composite polyol is a composition of high-activity polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 2.4:4:1.6.
[0077] The highly active polyether polyol is a propylene oxide-ethylene oxide copolyether triol with a functionality of 3, an ethylene oxide chain mass fraction of 16.2%, and a number average molecular weight of 5200 Da. It was purchased from Changhua Chemical Technology Co., Ltd. and is a CHE-330N product.
[0078] The polyester polyol is polyadipic acid polyester diol with a number average molecular weight of 4000 Da, which is purchased from the HY series of corresponding molecular weight products sold by Shandong Suihua Biotechnology Co., Ltd.
[0079] The modified polyol is a PIPA modified polyether polyol with a number average molecular weight of 6000 Da and a viscosity of 2200 mPa·s at 25° C. The SP50-04 product was purchased from Shell.
[0080] The tackifying resin is terpene phenolic resin, which is purchased from 803L terpene phenolic tackifying resin product sold by Shandong Changyao New Materials Co., Ltd.
[0081] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 5.8 parts of carbon fiber to 120 parts of deionized water, adding 1.4 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 1.6 parts of tetraethyl orthosilicate and 0.2 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 4.2 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 1.6 parts of succinic anhydride, 0.26 parts of sodium dodecylbenzene sulfonate and 0.18 parts of titanate couple The mixture was heated to 68°C and kept warm for 2.5 hours to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 1 part of zinc nitrate were added to 80 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 3.2 parts of 2,5-dihydroxyterephthalic acid and 0.35 parts of titanium dioxide (40 parts in total) was added dropwise for 1 hour, and the mixture was heated to 75°C and stirred at 100 rpm for 4 hours, and then the mixture was heated to 140°C and stirred at 60 rpm for 28 hours. After completion, the mixture was naturally cooled to room temperature, and the product was centrifuged, filtered, washed and dried to obtain the product.
[0082] The titanate coupling agent is monoalkoxy titanate KR-TTS.
[0083] The average particle size of titanium dioxide is 10.5 nm.
[0084] The carbon fiber is chopped carbon fiber with an average diameter of 6.5 μm and an average length of 18.2 μm, and is purchased from Shanghai Lishuo Composite Materials Co., Ltd.
[0085] The plasticizer is a composition of dioctyl phthalate and triethyl citrate, and the mass ratio of the two is 4:1.
[0086] The chain extender is 1,2-propylenediamine; the catalyst is dibutyltin dioctoate.
[0087] The dispersant is a composition of lauryl alcohol polyoxyethylene ether and cocoyl betaine, with a mass ratio of 4:0.5; lauryl alcohol polyoxyethylene was purchased from the MOA-5 model product sold by Hai'an Guoyun Chemical Co., Ltd.; cocoyl betaine was purchased from the cocamidopropyl betaine CAB-35 product sold by Jiangsu Haolong Chemical Co., Ltd.
[0088] The wetting agent is a composition of sodium stearate and sodium lauryl sulfate, and the mass ratio of the two is 4.5:2.
[0089] The isocyanate is diphenylmethane diisocyanate.
[0090] The second aspect of this embodiment provides a method for preparing the above-mentioned hot melt adhesive for electronic products, which specifically includes the following steps: S1: Add complex polyols, catalysts, plasticizers and chain extenders into a reaction container, heat to 70°C, stir at 80rpm for 4h, and then dry and remove water to a water content of ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 140rpm and heat to 120°C, keep warm for 4.5h, take out the product after the reaction is completed, vacuum degas for 1h and transfer to a storage container for drying under inert gas protection.
[0091] Example 3
[0092] Example 3 The first aspect provides a hot melt adhesive for electronic products. The raw materials, calculated by mass, are: 85 parts of complex polyol, 12.2 parts of tackifying resin, 23.5 parts of modified filler, 8.5 parts of plasticizer, 1.8 parts of chain extender, 6.2 parts of dispersant, 0.8 parts of catalyst, 4.2 parts of wetting agent, and 26 parts of isocyanate.
[0093] The composite polyol is a composition of high-activity polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 2.4:4:1.6.
[0094] The highly active polyether polyol is a propylene oxide-ethylene oxide copolyether triol with a functionality of 3, an ethylene oxide chain mass fraction of 16.2%, and a number average molecular weight of 5200 Da. It was purchased from Changhua Chemical Technology Co., Ltd. and is a CHE-330N product.
[0095] The polyester polyol is polyadipic acid polyester diol with a number average molecular weight of 4000 Da, which is purchased from the HY series of corresponding molecular weight products sold by Shandong Suihua Biotechnology Co., Ltd.
[0096] The modified polyol is a PIPA modified polyether polyol with a number average molecular weight of 6000 Da and a viscosity of 2200 mPa·s at 25° C. The SP50-04 product was purchased from Shell.
[0097] The tackifying resin is terpene phenolic resin, which is purchased from 803L terpene phenolic tackifying resin product sold by Shandong Changyao New Materials Co., Ltd.
[0098] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 6 parts of carbon fiber to 120 parts of deionized water, adding 1.1 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 1.3 parts of tetraethyl orthosilicate and 0.12 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 4 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 2 parts of succinic anhydride, 0.36 parts of sodium dodecylbenzene sulfonate and 0.11 parts of titanate coupling agent, The temperature was raised to 68°C and kept for reaction for 2.5 hours to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 1 part of zinc nitrate were added to 80 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 3.2 parts of 2,5-dihydroxyterephthalic acid and 0.35 parts of titanium dioxide (40 parts in total) was added dropwise for 1 hour, and the temperature was raised to 75°C and stirred at 100 rpm for reaction for 4 hours, and then the temperature was continued to be raised to 140°C and stirred at 60 rpm for reaction for 28 hours. After completion, it was naturally cooled to room temperature, and the product was centrifuged, filtered, washed and dried to obtain the product.
[0099] The titanate coupling agent is monoalkoxy titanate KR-TTS.
[0100] The average particle size of titanium dioxide is 6.2 nm.
[0101] The carbon fiber is chopped carbon fiber with an average diameter of 7.8 μm and an average length of 15.5 μm, and is purchased from Shanghai Lishuo Composite Materials Co., Ltd.
[0102] The plasticizer is a composition of dioctyl phthalate and triethyl citrate, and the mass ratio of the two is 4:1.
[0103] The chain extender is 1,2-propylenediamine; the catalyst is dibutyltin dioctoate.
[0104] The dispersant is a composition of lauryl alcohol polyoxyethylene ether and cocoyl betaine, with a mass ratio of 4:0.5; lauryl alcohol polyoxyethylene was purchased from the MOA-5 model product sold by Hai'an Guoyun Chemical Co., Ltd.; cocoyl betaine was purchased from the cocamidopropyl betaine CAB-35 product sold by Jiangsu Haolong Chemical Co., Ltd.
[0105] The wetting agent is a composition of sodium stearate and sodium lauryl sulfate, and the mass ratio of the two is 4.5:1.5.
[0106] The isocyanate is diphenylmethane diisocyanate.
[0107] The second aspect of this embodiment provides a method for preparing the above-mentioned hot melt adhesive for electronic products, which specifically includes the following steps: S1: Add complex polyols, catalysts, plasticizers and chain extenders into a reaction container, heat to 70°C, stir at 80rpm for 4h, and then dry and remove water to a water content of ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 140rpm and heat to 120°C, keep warm for 4.5h, take out the product after the reaction is completed, vacuum degas for 1h and transfer to a storage container for drying under inert gas protection.
[0108] Example 4
[0109] Example 4 The first aspect provides a hot melt adhesive for electronic products. The raw materials, calculated by mass, are: 75 parts of complex polyol, 18 parts of tackifying resin, 18 parts of modified filler, 8.5 parts of plasticizer, 1.8 parts of chain extender, 9.5 parts of dispersant, 0.8 parts of catalyst, 4.2 parts of wetting agent, and 22 parts of isocyanate.
[0110] The composite polyol is a composition of high-activity polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 1.8:5.5:1.3.
[0111] The highly active polyether polyol is a propylene oxide-ethylene oxide copolyether triol with a functionality of 3, an ethylene oxide chain mass fraction of 16.2%, and a number average molecular weight of 5200 Da. It was purchased from Changhua Chemical Technology Co., Ltd. and is a CHE-330N product.
[0112] The polyester polyol is polyadipic acid polyester diol with a number average molecular weight of 4000 Da, which is purchased from the HY series of corresponding molecular weight products sold by Shandong Suihua Biotechnology Co., Ltd.
[0113] The modified polyol is a PIPA modified polyether polyol with a number average molecular weight of 6000 Da and a viscosity of 2200 mPa·s at 25° C. The SP50-04 product was purchased from Shell.
[0114] The tackifying resin is terpene phenolic resin, which is purchased from 803L terpene phenolic tackifying resin product sold by Shandong Changyao New Materials Co., Ltd.
[0115] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 5.5 parts of carbon fiber to 120 parts of deionized water, adding 1.5 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 1.8 parts of tetraethyl orthosilicate and 0.19 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 4.5 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 1.5 parts of succinic anhydride, 0.21 parts of sodium dodecylbenzene sulfonate and 0.19 parts of titanate coupling agent. The mixture was heated to 68°C and kept warm for 2.5 hours to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 1 part of zinc nitrate were added to 80 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 3.2 parts of 2,5-dihydroxyterephthalic acid and 0.35 parts of titanium dioxide (40 parts in total) was added dropwise for 1 hour, and the mixture was heated to 75°C and stirred at 100 rpm for 4 hours, and then the mixture was heated to 140°C and stirred at 60 rpm for 28 hours. After completion, the mixture was naturally cooled to room temperature, and the product was centrifuged, filtered, washed and dried to obtain the product.
[0116] The titanate coupling agent is monoalkoxy titanate KR-TTS.
[0117] The average particle size of titanium dioxide is 14.5 nm.
[0118] The carbon fiber is chopped carbon fiber with an average diameter of 5.6 μm and an average length of 19.5 μm, and is purchased from Shanghai Lishuo Composite Materials Co., Ltd.
[0119] The plasticizer is a composition of dioctyl phthalate and triethyl citrate, and the mass ratio of the two is 3:2.
[0120] The chain extender is 1,2-propylenediamine; the catalyst is dibutyltin dioctoate.
[0121] The dispersant is a composition of lauryl alcohol polyoxyethylene ether and cocoyl betaine, with a mass ratio of 3:0.8; lauryl alcohol polyoxyethylene was purchased from the MOA-5 model product sold by Hai'an Guoyun Chemical Co., Ltd.; cocoyl betaine was purchased from the cocamidopropyl betaine CAB-35 product sold by Jiangsu Haolong Chemical Co., Ltd.
[0122] The wetting agent is a composition of sodium stearate and sodium lauryl sulfate, and the mass ratio of the two is 4:1.9.
[0123] The isocyanate is diphenylmethane diisocyanate.
[0124] The second aspect of this embodiment provides a method for preparing the above-mentioned hot melt adhesive for electronic products, which specifically includes the following steps: S1: Add complex polyols, catalysts, plasticizers and chain extenders into a reaction container, heat to 70°C, stir at 80rpm for 4h, and then dry and remove water to a water content of ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 140rpm and heat to 120°C, keep warm for 4.5h, take out the product after the reaction is completed, vacuum degas for 1h and transfer to a storage container for drying under inert gas protection.
[0125] Comparative Example 1
[0126] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the hot melt adhesive for electronic products, in parts by mass, are: 70.5 parts of complex polyol, 10.8 parts of tackifying resin, 32.5 parts of modified filler, 8.5 parts of plasticizer, 1.8 parts of chain extender, 7.6 parts of dispersant, 0.8 parts of catalyst, 4.2 parts of wetting agent, and 20.5 parts of isocyanate.
[0127] Comparative Example 2
[0128] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the hot melt adhesive for electronic products, in parts by mass, are: 95.5 parts of complex polyol, 14.8 parts of tackifying resin, 5.5 parts of modified filler, 8.5 parts of plasticizer, 1.8 parts of chain extender, 7.6 parts of dispersant, 0.8 parts of catalyst, 4.2 parts of wetting agent, and 28.5 parts of isocyanate.
[0129] Comparative Example 3
[0130] The specific implementation of this comparative example is basically the same as that of Example 1, except that the highly active polyether polyol is propylene oxide-ethylene oxide copolyether diol with a functionality of 2, purchased from VORANOL™ CP3700 model product sold by Dow Chemical.
[0131] Comparative Example 4
[0132] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite polyol is a composition of highly active polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 1:6:2.5.
[0133] Comparative Example 5
[0134] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite polyol is a composition of highly active polyether polyol, polyester polyol and modified polyol, and the mass ratio of the three is 5:2:0.5.
[0135] Comparative Example 6
[0136] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 5.8 parts of carbon fiber to 120 parts of deionized water, adding 0.5 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 0.8 parts of tetraethyl orthosilicate and 0.1 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 6.5 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 1 part of succinic anhydride, 0.15 parts of dodecylbenzene Sodium sulfonate and 0.09 parts of titanate coupling agent, heated to 68°C and kept warm for 2.5 hours to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 1 part of zinc nitrate are added to 80 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 3.2 parts of 2,5-dihydroxyterephthalic acid and 0.35 parts of titanium dioxide (40 parts in total) is added dropwise for 1 hour, and the temperature is raised to 75°C and stirred at 100 rpm for 4 hours, and then the temperature is continued to be raised to 140°C and stirred at 60 rpm for 28 hours. After completion, it is naturally cooled to room temperature, the product is centrifuged and filtered, washed and dried to obtain.
[0137] Comparative Example 7
[0138] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: adding 5.8 parts of carbon fiber to 120 parts of deionized water, adding 1.4 parts of ethanol and adjusting the pH to 9.5 with ammonia water, then adding 1.6 parts of tetraethyl orthosilicate and 0.2 parts of isopropanol and heating to 72°C for 2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding 4.2 parts of pretreated carbon fiber to 120 parts of DMF solution, adding 1.6 parts of succinic anhydride, 0.26 parts of dodecylbenzene Sodium sulfonate and 0.18 parts of titanate coupling agent, heated to 68°C and kept warm for 2.5 hours to obtain pretreated particles; S3: 4.5 parts of pretreated particles and 0.8 parts of zinc nitrate are added to 100 parts of DMF solution and stirred to mix evenly, and then a DMF solution containing 2.1 parts of 2,5-dihydroxyterephthalic acid and 0.12 parts of titanium dioxide (30 parts in total) is added dropwise for 1 hour, and the temperature is raised to 75°C and stirred at 100 rpm for 4 hours, and then the temperature is continued to be raised to 140°C and stirred at 60 rpm for 28 hours. After completion, it is naturally cooled to room temperature, the product is centrifuged and filtered, washed and dried to obtain.
[0139] Comparative Example 8
[0140] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 25 nm; the carbon fiber is chopped carbon fiber with an average diameter of 12.5 μm and an average length of 26.8 μm, which is purchased from Shanghai Lishuo Composite Materials Co., Ltd.
[0141] Performance Evaluation
[0142] Mechanical properties: The elongation at break of the polyurethane hot melt adhesives prepared in the embodiments and comparative examples was tested using a universal testing machine at 25° C. and 50% relative humidity. The test values were averaged over 10 tests and recorded in Table 1.
[0143] Adhesion: With reference to standard GB / T 2791-1995, the polyurethane hot melt adhesives of the embodiments and comparative examples were subjected to T-peel strength adhesion test to measure final adhesion. The test values were averaged over 10 tests and recorded in Table 1.
[0144] Waterproofness: The polyurethane hot melt adhesives prepared in the embodiments and comparative examples were cured to obtain samples of 2 cm×2 cm×0.2 cm. The surface waterproof performance of the hot melt adhesive was tested by the sessile drop method. The test drop size was 2.5 μL and the test time was 15 s. The surface water contact angle was obtained. The test value was the average of 10 tests and recorded in Table 1.
[0145] Aging resistance: After curing the polyurethane hot melt adhesives prepared in the embodiments and comparative examples, samples of 2 cm × 2 cm × 0.2 cm were prepared and placed in a constant temperature and humidity chamber at 68 ± 2 ° C and 75 ± 3% relative humidity for 6 months. After 6 months, it was recorded whether the samples had yellowing, oxidation, cracking, blistering and hydrolysis damage. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group and the qualified rate of the samples was recorded and recorded in Table 1.
[0146] Corrosion resistance: After the polyurethane hot melt adhesives prepared in the examples and comparative examples were cured, samples of 2 cm × 2 cm × 0.2 cm were prepared for salt spray resistance test. The test environment temperature was 35 ± 2 ° C, the humidity was 98 ± 2%, the test solution was 5wt% NaCl solution, and the test time was 200 h. After the test, the cured hot melt adhesive was observed for corrosion, shedding, cracking and blistering. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.
[0147] Table 1 Performance test results
[0148]
[0149] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 to 4 of the present application have obvious advantages over Comparative Examples 1 to 8 in terms of mechanical properties, bonding properties, waterproof properties, corrosion resistance and aging resistance. This is mainly due to the combined effect of the specific polyol composition, modified filler and other matching schemes specified in the present application. Comparative Examples 1 to 8 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A hot melt adhesive for electronic products, characterized in that: The raw materials are as follows: 60-90 parts of compound polyol, 10-20 parts of tackifying resin, 15-25 parts of modified filler, 6-10 parts of plasticizer, 1.5-3 parts of chain extender, 5-12 parts of dispersant, 0.5-1.5 parts of catalyst, 3-5 parts of wetting agent, and 20-30 parts of isocyanate. The mass ratio of the composite polyol, isocyanate and tackifying resin is (75-85): (22-26): (12-18); The mass of the composite polyol, modified filler and dispersant is (75-85): (18-24): (6-10); The composite polyol is a composition of high-activity polyether polyol, polyester polyol and modified polyol; the mass ratio of the high-activity polyether polyol, polyester polyol and modified polyol is (1.8-2.4): (4-5.5): (1.3-1.6); The functionality of the highly active polyether polyol is 3; The number average molecular weight of the highly active polyether polyol is 4000-6000Da; The modified polyol is PIPA modified polyether polyol; The tackifying resin is at least one of terpene phenolic resin, dicyclopentadiene resin, and C5 / C9 copolymerized petroleum resin; The preparation method of the modified filler comprises the following steps: S1: adding carbon fiber to deionized water, adding ethanol and adjusting the pH to 9-10 with ammonia water, then adding tetraethyl orthosilicate and isopropanol and heating to 70-75°C for 2-2.5 hours, after completion, centrifuging and filtering the product, washing with deionized water, and drying to obtain pretreated carbon fiber; S2: adding the pretreated carbon fiber to DMF solution, adding succinic anhydride, sodium dodecylbenzene sulfonate and titanate coupling agent, heating to 65-70°C for 2-3 hours, Pretreated particles are obtained; S3: the pretreated particles and zinc nitrate are added to the DMF solution and stirred to mix evenly, and then the DMF solution containing 2,5-dihydroxyterephthalic acid and titanium dioxide is added dropwise for 1-1.5 hours, and the temperature is raised to 70-80°C and stirred at 80-120 rpm for 3-5 hours, and then the temperature is continued to be raised to 140-150°C and stirred at 50-70 rpm for 24-30 hours. After completion, the mixture is naturally cooled to room temperature, and the product is centrifuged, filtered, washed and dried to obtain the obtained product; The mass ratio of the carbon fiber, ethanol, tetraethyl orthosilicate and isopropyl alcohol is (5.5-6): (1-1.5): (1.2-1.8): (0.1-0.2); The mass ratio of the pretreated carbon fiber, succinic anhydride, sodium dodecylbenzene sulfonate and titanate coupling agent is (4-4.5): (1.5-2): (0.2-0.4): (0.1-0.2); The mass ratio of the pretreated particles, zinc nitrate, 2,5-dihydroxyterephthalic acid and titanium dioxide is (2-2.5): (0.8-1): (3-4): (0.2-0.4); The average particle size of the titanium dioxide is 5 to 15 nm; The chain extender is at least one of ethanolamine, ethylenediamine, diethanolamine, triethanolamine, and 1,2-propylenediamine; The carbon fiber is chopped carbon fiber; the average diameter of the chopped carbon fiber is 5-8 μm; the average length of the chopped carbon fiber is 15-20 μm.
2. The hot melt adhesive for electronic products according to claim 1, characterized in that: The highly active polyether polyol is propylene oxide-ethylene oxide copolyether triol.
3. The hot melt adhesive for electronic products according to claim 2, characterized in that: The mass fraction of ethylene oxide chain segments in the highly active polyether polyol is 10-20%.
4. The hot melt adhesive for electronic products according to claim 3, characterized in that: The number average molecular weight of the PIPA modified polyether polyol is 5500-7000 Da.
5. The hot melt adhesive for electronic products according to claim 4, characterized in that: The viscosity of the PIPA modified polyether polyol is 1500-3000 mPa·s at 25°C.
6. The hot melt adhesive for electronic products according to claim 5, characterized in that: The plasticizer is a composition of dioctyl phthalate and triethyl citrate; the mass ratio of the dioctyl phthalate and triethyl citrate is (3-4): (1-2).
7. The hot melt adhesive for electronic products according to claim 6, characterized in that: The dispersant is a composition of lauryl alcohol polyoxyethylene ether and coconut oil betaine; the mass ratio of lauryl alcohol polyoxyethylene ether to coconut oil betaine is (3-4): (0.5-0.8).
8. The hot melt adhesive for electronic products according to claim 7, characterized in that: The wetting agent is a composition of sodium stearate and sodium dodecyl sulfate; the mass ratio of the sodium stearate to sodium dodecyl sulfate is (4-4.5): (1.5-2).
9. A method for preparing a hot melt adhesive for electronic products according to any one of claims 1 to 8, characterized in that: The specific steps include: S1: Add complex polyol, catalyst, plasticizer and chain extender into the reaction vessel, raise the temperature to 65-75°C, stir at 60-80rpm for 3-5h, then dry and remove water until the water content is ≤0.02wt%; S2: Add the remaining raw materials, increase the speed to 120-160rpm and raise the temperature to 110-130°C, keep warm and react for 3-5h, take out the product after the reaction is completed, vacuum degassing for 0.5-1h and transfer to a storage container for drying under inert gas protection.
